2012
DOI: 10.1134/s0026893312020082
|View full text |Cite
|
Sign up to set email alerts
|

Association of MMP3, MMP9, ADAM33, and TIMP3 polymorphisms with chronic obstructive pulmonary disease and its progression

Abstract: PCR RFLP analysis was performed for 391 cases and 514 control individuals to analyze the contribu tion of polymorphisms of the matrix metalloproteinase genes MMP1 (-1607 G>GG, rs1799750; -519 A>G, rs494379), MMP2 (-735 C>T, rs2285053), MMP3 (-1171 5A>6A, rs35068180), MMP9 (-1562 C>T, rs3918242; 2660A>G, rs17576), MMP12 (-82 A>G, rs2276109), the disintegrin and metalloproteinase 33 gene ADAM33 (12418 A>G, rs2280091; 13491 C>G, rs2787094), and tissue inhibitors of metalloprotein ase genes TIMP2 (-418 G>C, rs8179… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 31 publications
(43 reference statements)
1
28
0
1
Order By: Relevance
“…In addition to augmenting inflam matory response and proteolysis in the lungs, ADAM33 is also involved in angiogenesis [32]. Several studies have previously reported that ADAM33 polymor phisms were associated with COPD and bronchial asthma [12,[32][33][34]; our own data confirmed such an association in COPD patients from Bashkortostan [15]. Our results suggest that ADAM33 is an important factor involved in the pathogenesis of respiratory diseases induced by smoking or industrial dust and aerosols.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition to augmenting inflam matory response and proteolysis in the lungs, ADAM33 is also involved in angiogenesis [32]. Several studies have previously reported that ADAM33 polymor phisms were associated with COPD and bronchial asthma [12,[32][33][34]; our own data confirmed such an association in COPD patients from Bashkortostan [15]. Our results suggest that ADAM33 is an important factor involved in the pathogenesis of respiratory diseases induced by smoking or industrial dust and aerosols.…”
Section: Discussionsupporting
confidence: 88%
“…TIMP3 is located on chro mosome 22 at site 22q12.1 q13.2; the (-1296T>C) polymorphisms in the gene promoter is thought to affect the level of TIMP3 transcription [13]. It was reported that TIMP3 contributes to the resolution of acute inflammatory damage to lung tissue [41]; the data from our previous studies suggested that TIMP3 locus was associated with COPD and with lingering childhood pneumonia [15,42].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These results indicate that both MMP-3 and -10 may lead to different progression in smokers with COPD. Two genotyping studies indicated that MMP-3 polymorphisms associate with disease progression in COPD [36,37]. Another study showed the expression of the MMP-10 gene was increased in both small airways and the parenchyma surrounding small airways in association with progression of COPD [38].…”
Section: Discussionmentioning
confidence: 99%